Seasonal and Soil Microbiota Effects on the Adaptive Strategies of Wild Goitered Gazelles Based on the Gut Microbiota - Qin, Wen; Song, Pengfei; Zhang, Shoudong (Frontiers in Microbiology, 2022)
Seasonal variation in extreme environments is a threat to endangered species. The gut microbiota is important in the adaptive strategies of wild herbivores, and herbivores will contact the soil microbiota when they are feeding. However, there are no studies about the effects of soil microbiota on the gut microbiota of wild herbivores. Understanding the seasonal adaptive strategies of wild herbivores based on their gut microbiota and the effects of soil microbiota on the herbivorous gut microbiota is indispensable for making optimal conservation recommendations. To address those issues, we compared the diversity and functions of gut microbiota in goitered gazelles between winter and summer with a non-invasive fecal sampling method from the Qaidam Basin based on 16S rRNA V3-V4 regions. The data showed that seasonal variations caused the significant changes in gut microbiota at α-and β-diversity levels. The main gut microbial function was ‘Metabolism’. It showed significant seasonal changes. The goitered gazelles adapted to the seasonal changes by increasing the relative abundance of Firmicutes, Christensenellaceae, Bacteroides and the function about ‘Metabolism’ in the winter to improve the adaptability. We also compared the effects of soil microbiota on the gut microbiota between winter and summer, covering source tracking analysis and the seasonal differences in ecological assembly processes. The contribution of soil microbiota on the gut microbiota of goitered gazelles was 5.3095% and 15.6347% in winter and summer, respectively, which was greater than on species of animals living underground. Seasonal variation also influenced the ecological processes of microbiota both in the gut and soil. Due to the differences in environments, the ecological processes between fecal microbiota and soil microbiota showed significant differences, and they were dominated by stochastic processes and deterministic processes, respectively. The soil microbiota has contributed to the gut microbiota, but not a decisive factor. Our research laid the foundation on the seasonal and soil microbiota effects on the adaptive strategies of goitered gazelles, and is the first study to explain the soil microbiota influence on the gut microbiota of wild herbivores.